Mid-term development of the right ventricle in competitive athletes. (December 2018) - Krumm, Patrick; Krauß, Stefan; Mangold, Stefanie; Zitzelsberger, Tanja; Klumpp, Bernhard D; Nikolaou, Konstantin; Nieß, Andreas M; Kramer, Ulrich; Burgstahler, Christof
Background: Long-term intensive training induces physiological, morphological, and functional adaption of the athlete's heart. Purpose: To evaluate the development of athlete's heart during a mid-term follow-up of competitive athletes using cardiac magnetic resonance (CMR). Material and Methods: Eighteen competitive long-distance runners and triathletes (age 43 ± 13 years, 3 women) were prospectively examined in a longitudinal follow-up study 5.05 ± 0.6 years after baseline. CMR at 1.5-T was performed for functional and late gadolinium enhancement (LGE) imaging. Left ventricular (LV) and right ventricular (RV) end-diastolic volume (LVEDV, RVEDV) as well as ejection fraction (LVEF, RVEF), LV myocardial mass (LVMM), and atrial sizes were determined and compared to baseline in matched pairs statistics for paired difference. Results: LVEDV (197 ± 38 mL vs. 196 ± 38 mL, paired difference −0.9 mL, P = 0.7) and LVEF (62 ± 7% vs. 62 ± 5%, paired difference 0.1%, P = 0.9) did not change during the follow-up period, whereas LVMM increased significantly (149 ± 31 g vs.164 ± 32 g, paired difference 14 g, P < 0.0001). RVEDV significantly increased from 221 ± 47 mL at baseline to 230 ± 52 mL (paired difference 10 mL, P = 0.0033). RVEF decreased from baseline 57 ± 8% to 53 ± 7% (paired difference −3%, P = 0.0234). Left atrial size showed no significant changes (24 ± 5 cm 2 vs. 25 ± 6 cm 2, paired difference 0.5 cm 2, P = 0.17) and right atrial size increased significantly (30 ± 5 cm 2 vs. 32 ± 4 cm 2, paired difference 2 cm 2, P = 0.0054). Conclusion: This study supports the theory of ongoing remodeling in an athlete's heart. Predominantly the right heart can further enlarge in a mid-term period. This response seems not linearly dependent on a steady, decreased, or increased training volume.